An effective method to produce 7-epitaxol from taxol in HCO3–. Issue 15 (1st August 2020) - Liu, Yanjie; Ma, Xiaoyu; Zhou, Mengkai; Hao, Xiaoran; Zhu, Xudong
Graphical abstract: Abstract: It is known that 7-epitaxol has much stronger cytotoxicity than taxol does. However, the content of 7-epitaxol in yew is much less than taxol, which makes it more costly to obtain. We describe here a method to effectively convert taxol to 7-epitaxol. The key condition for reaction needs NaHCO3 in solvent acetonitrile (ACN). The conversion rate can be over 82%.